Augmented Reality Assisted Flipped Classroom Model Against Students' Mathematical Problem-Solving Ability - Raras Cahyaningrum; Windia Hadi (Jurnal Inovasi Matematika, 2023)
The use of Augmented Reality media is still rarely used in schools due to the lack of teachers’ innovation in classroom learning. Augmented Reality is a technology that combines three-dimensional real objects directly so that they can influence mathematical problem-solving abilities. The objective of this study is to determine the effect of the Augmented Reality-assisted Flipped Classroom model on students’ mathematical problem-solving abilities. This research is a quasi-experimental study with a posttest-only control group design. The population of this study consists of all students of class VIII. Samples are taken using the Cluster Random Sampling technique. The samples consist of experimental and control classes, each of which consists of 35 students. The description test given at the end of the study is used as a data collection method. According to the posttest results, the average problem-solving score using the Flipped Classroom model with Augmented Reality is 69.03, while the average score using the Flipped Classroom model without Augmented Reality is 58.97. This shows that students who use the Flipped Classroom model with Augmented Reality have better mathematical problem-solving abilities compared to the Flipped Classroom model without Augmented Reality. Therefore, there is an effect of using Augmented Reality media on mathematical problem-solving abilities.